Chitin Triggers Tissue-Specific Immunity in Wheat Associated With Fusarium Head Blight - Hao, Guixia; Tiley, Helene; McCormick, Susan (Frontiers in Plant Science, 2022)
Fusarium graminearum is one of the primary causal agents of Fusarium head blight (FHB) on wheat and barley. FHB reduces grain yield and contaminates grain with various mycotoxins, including deoxynivalenol (DON). DON acts as a virulence factor to promote the fungus passing the rachis node and spreading throughout the head of wheat but not barley. Reactive oxygen species (ROS) are one of the earliest defense responses during plant and pathogen interactions. However, the complex roles of ROS during FHB development remain unclear. We investigated immune responses in wheat triggered by chitin, a major component of fungal cell walls. Although no ROS burst was detected in chitin-treated wheat leaves from eight tested varieties, a robust ROS peak was triggered by chitin in tested barley leaves. Interestingly, ROS were induced by chitin in wheat rachises and rachis nodes, which are critical barriers for FHB spread in wheat. We demonstrated that ROS were induced in wheat rachis nodes from both FHB susceptible and resistant wheat varieties. Further, we showed different defense gene expression patterns in rachis nodes and wheat heads treated with chitin, and wheat heads inoculated with F. graminearum. Our study showed the tissue specific immune responses induced by chitin in wheat, which may play an important role during F. graminearum infection.